Risk factors of self-medication with antibiotics for acute pharyngitis - Mikołaj Porzak; Michał Dacka; Mateusz Sobczyk; Alicja Sodolska; Daria Żuraw; Kacper Jasiński; Paulina Oleksa; Robert Porzak; Magdalena Kubicka-Dębiec (Kazimierz Wielki University, 2024)
Background: Self-medicating with antibiotics is prevalent in low- and middle-income nations. This research sought to assess the perspectives on antibiotic usage and self-medication in case of acute pharyngitis, as well as the factors linked to self-medication among patients of a family doctor's clinic in Lublin, Poland. Methods: A original, fully anonymous survey was conducted among patients of a family doctor's clinic in Lublin. The descriptive statistics of answers in questionnaires and Automatic Linear Modeling Regression (LINEAR) was applied to point out the most significant predictors of the antibiotics misuse. Results: A response number of 262 participants was obtained. About 15,6% (41/262) respondents had self-medicated during the last year due to acute pharyngitis symptoms. We have identified the following important risk factors of anti-health behaviours connected with self-medication: frequent occurrence of symptoms of acute pharyngitis, frequent receiving antibiotics on prescription, frequent diagnosing a bacterial cause of sore throat, higher sensitivity to pain and lower education level. Surprisingly our research shows that women present lower sensitivity to pain than men in case of pain connected with acute pharyngitis. Conclusion: There is a need for greater attention paid to the education of the patients presenting the aforementioned risk factors. Education should focus on the risks to the patients connected with antimicrobial resistance.